Sistem Informasi Berbasis Web Untuk Memonitoring Perangkat Internet of Things (IoT) Menggunakan Node-Red - Mulyawan, M Fikri; Batubara, Mona Arif Muda; Pradipta, Rio Ariestia (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2023)
Information systems in monitoring Internet of Things (IoT) devices in this advanced telecommunications world are very important, where we can see in real-time the data displayed by the device. This is very useful in improving the performance and efficiency of the development party. The use of this technology makes it easier to anticipate error that occurs to system Internet of Things (IoT) devices. By being displayed using a dashboard, it makes it easier for users to read data provided by the Internet of Things devices. In this study, the author develops a Dashboard information system for the Internet of Things Device system. Data from the system will be sent to a database which will then be displayed using the Node-Red tools. This tool is a middleware that connects the Internet of Things (IoT) devices with a database, the results of reading the Internet of Things system will be stored in the database and the results can be seen through the Dashboard in real-time. The result of the measurement if it exceeds the standard limit that has been determined, will give an alert in the form of a notification in the Email.